2015
DOI: 10.1158/1940-6207.capr-14-0324
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Trial of Green Tea Catechins for Prostate Cancer Prevention

Abstract: Preclinical, epidemiological and prior clinical trial data suggest that green tea catechins (GTCs) may reduce prostate cancer (PCa) risk. We conducted a placebo-controlled, randomized clinical trial of Polyphenon E® (PolyE), a proprietary mixture of GTCs, containing 400 mg (–)-epigallocatechin-3-gallate (EGCG) per day, in 97 men with high-grade prostatic intraepithelial neoplasia (HGPIN) and/or atypical small acinar proliferation (ASAP). The primary study endpoint was a comparison of the cumulative one-year PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 59 publications
2
98
1
1
Order By: Relevance
“…This study found a lower rise in PSA in the intervention group, as did another study supplementing Polyphenon E instead of GT [200]. In a similarly designed study comparing EGCG extract versus placebo, a significant decrease was obtained only for the combined endpoint "carcinoma plus atypical small acinar proliferations" but not for prostate cancer alone [201]. Contrary to these results, Gontero et al [202] reported an increase in prostate cancer incidence in patients with high grade prostatic intraepithelial neoplasia (HGPIN) or atypical small acinar proliferations (ASAP), after supplementing the diet with selenium, lycopene and GTE.…”
Section: Prostatic Cancer-additional Evidencementioning
confidence: 55%
See 1 more Smart Citation
“…This study found a lower rise in PSA in the intervention group, as did another study supplementing Polyphenon E instead of GT [200]. In a similarly designed study comparing EGCG extract versus placebo, a significant decrease was obtained only for the combined endpoint "carcinoma plus atypical small acinar proliferations" but not for prostate cancer alone [201]. Contrary to these results, Gontero et al [202] reported an increase in prostate cancer incidence in patients with high grade prostatic intraepithelial neoplasia (HGPIN) or atypical small acinar proliferations (ASAP), after supplementing the diet with selenium, lycopene and GTE.…”
Section: Prostatic Cancer-additional Evidencementioning
confidence: 55%
“…They argue that pharmacology data for neutraceuticals like Polyphenon E and food supplements like GT should be included in any study protocol, as well as for extending these studies to realistic clinical time scenarios relevant for tumor progression (i.e., 5 to 20 years observation). A preliminary evaluation for Polyphenon E versus placebo after one year follow up found no effect [201].…”
Section: Prostatic Cancer-additional Evidencementioning
confidence: 99%
“…Nevertheless few studies on the chemopreventive role of EGCG have yielded inconsistent results. A study performed by Kumar et al showed that daily intake of a standardized, decaffeinated catechin mixture containing 400 mg EGCG per day for 1 year was well tolerated but did not reduce the likelihood of prostate cancer in men with baseline highgrade prostatic intraepithelial neoplasia or atypical small acinar proliferation [20]. Most of the clinical trials have certain limitations i.e., short duration and low participation which need to be considered before pronouncing the drug's efficacy or toxicity.…”
Section: Anti Proliferative Role Of Egcgmentioning
confidence: 99%
“…However, certain studies have also yielded inconsistent results. Another study on prostate intraepithelial neoplasia patients, showed that daily intake of EGCG for a year was well tolerated but did not reduce the likelihood of prostate cancer in men [20]. Individual metabolic differences Expert Opinion on Therapeutic Patents result in differential response; duration and cost associated with clinical trials, limit the use of EGCG for treating diseases and hence call for the need of personalized medicine.…”
Section: Expert Opinionmentioning
confidence: 99%
“…19 However, the recently published results of an American trial, randomising 97 men with precancerous prostatic lesions to receive polyphenon E (green tea extract) or placebo, revealed no significant difference in prostate cancer incidence. 20 Although not proven dangerous, lycopene and polyphenol have not been proven useful and their use should not be encouraged. …”
Section: Lycopene and Polyphenolsmentioning
confidence: 99%